Closing the methane mass balance for an old closed Danish landfill. (1st February 2020) - Fjelsted, L.; Christensen, A.G.; Larsen, J.E.; Kjeldsen, P.; Scheutz, C.
Highlights: Establishment of a methane mass balance for an old landfill. Methane mass balance is an important concept in landfill gas management planning. Lateral landfill gas migration despite bottom and side liners. Oxidation of lateral migrating methane in unsaturated gravel outside the landfill. Oxidation in landfill cover represented about two third of total methane generation. Abstract: In this study, a methane (CH4 ) mass balance was established for Hedeland landfill. CH4 generation rates were modelled using a multiphase first-order decay model (The Afvalzorg model) and determined at between 57 and 79 kg h −1 . The CH4 emission rate was quantified at between 2 and 14 kg h −1, using the tracer gas dispersion method and the CH4 gas recovery efficiency was between 8 and 21%. At three places along the perimeter of the landfill, gas remediation systems have been installed to protect the residential houses from any risk of migrating landfill gas. About 0.76 kg h −1 of CH4 was extracted from these three remediation systems. Using a carbon mass balance for the lateral migrating landfill gas showed a fractional oxidation of about 78%, which corresponded to a CH4 flux of 3.5 kg h −1 from the three remediation systems, including the oxidised CH4 . The total lateral CH4 flux (un-oxidised) from the total landfill perimeter was estimated at between 6.9 and 10.4 kg h −1 . CH4 oxidation efficiency in the landfill cover soil, determined from stable carbon isotope analyses, was found to be between 12% and 92%. This resulted in an average CH4 oxidation rate of 32 kg h −1, using an average CH4 emission rate of 8 kg h −1 . CH4 surface screenings and surface flux measurements supported the hypothesis that oxidation efficiency was in the higher range and that oxidation could close the CH4 mass balance.